Two homologous LHY pairs negatively control soybean drought tolerance by repressing the abscisic acid responses. Issue 5 (23rd November 2020) - Wang, Kai; Bu, Tiantian; Cheng, Qun; Dong, Lidong; Su, Tong; Chen, Zimei; Kong, Fanjiang; Gong, Zhizhong; Liu, Baohui; Li, Meina
Summary: The circadian clock plays essential roles in diverse plant biological processes, such as flowering, phytohormone biosynthesis and abiotic stress responses. The manner in which circadian clock genes regulate drought stress responses in model plants has been well established, but comparatively little is known in crop species, such as soybean, a major global crop. This paper reports that the core clock components GmLHYs, the orthologues of CCA1/LHY in Arabidopsis, negatively control drought tolerance in soybean. The expressions of four GmLHY s were all induced by drought, and the quadruple mutants of GmLHY s demonstrated significantly improved drought tolerance. Transcriptome profiling suggested that the abscisic acid (ABA) signaling pathway is regulated by GmLHY s to respond to drought tolerance. Genetic dissections showed that two homologous pairs of LHY1a and LHY1b redundantly control the drought response. Functional characterization of LHY1a and LHY1b in Arabidopsis and soybean further supported the notion that GmLHY s can maintain cellular homeostasis through the ABA signaling pathway under drought stress. This study improves our understanding of the underlying molecular mechanisms on soybean drought tolerance. Furthermore, the two homologues of LHY1a and LHY1b provide alternative targets for genome editing to rapidly generate mutant alleles in elite soybean cultivars to enhance their drought tolerance.